Managing Projects in Trouble : Achieving Turnaround and Success. - Kliem, Ralph L. (CRC Press, 2011)
Whether you use budget, schedule, quality, or other criteria, the statistics by think tanks, institutes, associations, and other trade organizations all point to one inescapable conclusion: your project has a greater chance of getting into trouble than staying out of it. Based on the lessons learned by the author during a quarter of a century of leading projects to successful conclusions, Managing Projects in Trouble: Achieving Turnaround and Success unveils the five secrets to ensuring success--even for projects seemingly doomed to fail. Using numerous flow diagrams and checklists, it explain.